Multidimensional Clinical Challenges in a Female with Chronic Epilepsy on Phenytoin: A Case Report: - Nurulita, Syafira Laila; Lamsudin, Rusdi (Universitas Ahmad Dahlan, 2025)
Epilepsy is a long-standing neurological disorder defined by recurrent, unprovoked seizures, affecting more than 50 million individuals globally and influencing physical, mental, and social aspects of life. Continuous administration of antiepileptic drugs (AEDs) such as phenytoin is a common therapeutic strategy; however, prolonged use may result in adverse effects that complicate treatment. This case report describes a 40-year-old woman with epilepsy since the age of four, presenting with recurrent seizures, impaired memory, headaches, and sexual dysfunction. Her most recent event was an absence seizure accompanied by upward eye deviation and tongue biting. Electroencephalography (EEG) demonstrated generalized spike-and-wave patterns. The patient was treated with phenytoin and folic acid, with the recent addition of clobazam, leading to favorable outcomes, including reduced seizure frequency, improved sleep, and diminished anxiety and dizziness. A persistent reduction in libido, first noted during adolescence, was suspected to be associated with long-term phenytoin use. Additionally, dental problems such as caries and tooth impaction were believed to worsen headache intensity. This case emphasizes the need for a comprehensive approach to epilepsy care, considering psychological conditions, cognitive impairment, and oral health. Prompt recognition of AED-related side effects and individualized treatment planning are essential to optimize patient outcomes.